PENGARUH PENYULUHAN DENGAN MEDIA PHANTOM DALAM MENINGKATKAN PENGETAHUAN KEBERSIHAN GIGI DAN MULUT PADA PEKERJA WANITA DI DUSUN SEMPOJA TAHUN 2025 - Jumiati Jumiati; Dony Hidayat; Heny Kurniawati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Introduction: Dental and oral hygiene is a condition that indicates that a person's oral cavity is free from dirt, such as plaque and calculus. Phantom media is included in the artificial object teaching aids. Objective: To determine the effect of counseling with phantom media in increasing knowledge of dental and oral hygiene among female workers in Sempoja Hamlet in 2025. Method: A quasi-experimental study with a one-group pretest and posttest design. The sample size was 30 people using the total sampling technique. Result: Knowledge before counseling with phantom media was in the less category for 30 respondents (100%) and the results of knowledge after counseling with phantom media were in the sufficient category for 7 respondents (23.3%) and 23 respondents (76.7%) were in the good category. Data analysis using the T Test with the help of SPSS 25 obtained a significant value of 0.000 <0.05. The calculated value> from the t table value (35.225>2.045). Conclusion: Counseling using phantom media can increase knowledge of dental and oral hygiene among female workers in Sempoja Hamlet.